2016
DOI: 10.1002/ejoc.201600385
|View full text |Cite
|
Sign up to set email alerts
|

1,6‐Addition Arylation of para‐Quinone Methides: An Approach to Unsymmetrical Triarylmethanes

Abstract: A 1,6‐addition arylation reaction of para‐quinone methides with α‐isocyanoacetamides and electron‐rich aromatic compounds under metal‐free conditions has been developed. BF3·Et2O plays two roles in the reaction: catalyzing the cyclization of α‐isocyanoacetamides to give oxazoles, and activating the para‐quinone methides to achieve the 1,6‐addition arylation process. The reaction shows good functional group tolerance, scalability, and regioselectivity. It is a consice protocol for the synthesis of diverse unsym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(25 citation statements)
references
References 62 publications
0
25
0
Order By: Relevance
“…In fact, among all products, the diethylamine-containing analogs 6i - l were synthesized in lower yields, which can be attributed to the lower stability of this isocyanide in acidic media. In all cases, the primary byproducts were the corresponding 5-aminooxazoles resulting from Lewis-acid-catalyzed chain-ring tautomerization of the isocyanides 3a - c (Gao et al, 2016). Consistent with reports by Zhu (Cuny et al, 2004; Wang et al, 2007), we also observed, as minor byproducts, the alcohols resulting from isocyanide addition to the aldehydes prior to oxazole formation ( 7) (Scheme 4).…”
Section: Resultsmentioning
confidence: 99%
“…In fact, among all products, the diethylamine-containing analogs 6i - l were synthesized in lower yields, which can be attributed to the lower stability of this isocyanide in acidic media. In all cases, the primary byproducts were the corresponding 5-aminooxazoles resulting from Lewis-acid-catalyzed chain-ring tautomerization of the isocyanides 3a - c (Gao et al, 2016). Consistent with reports by Zhu (Cuny et al, 2004; Wang et al, 2007), we also observed, as minor byproducts, the alcohols resulting from isocyanide addition to the aldehydes prior to oxazole formation ( 7) (Scheme 4).…”
Section: Resultsmentioning
confidence: 99%
“…2,6-Di-tert-butyl-4-((3a,7a-dihydro-1H-indol-3-yl)(phenyl)methyl)phenol ( 7): [41] Brown solid; 85% yield. To a solution of 2,6-di-tert-butyl-4-(phenyl(tosyl)methyl) phenol (45 mg, 0.1 mmol) in 1 mL methyl tert-butyl ether, Cs 2 CO 3 (36 mg, 0.01 mmol) and TBAB (3.6 mg, 0.01 mmol) were added.…”
Section: Representative Procedures For General Reaction Procedures For Synthesis Of Unsymmetrical Triarylmethanementioning
confidence: 99%
“…The main drawback is that most of the substrates should be prepared in advance, and therefore, multistep reaction processes are involved (Scheme 1c). [35][36][37][38][39][40][41][42][43][44][45][46][47] Although several three-component reactions have been reported for the synthesis of unsymmetrical triarylmethanes, the products were often limited to indolotriarylmethanes with moderate yields. [48][49][50][51][52][53][54][55][56][57][58] Therefore, the development of a straightforward method to build the completely unsymmetrical triarylmethanes in one step from readily available starting materials remains elusive.…”
Section: Introductionmentioning
confidence: 99%